2023
DOI: 10.1007/s10803-023-06034-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual-Motor Integration Deficits in 3q29 Deletion Syndrome

Abstract: Abstract3q29 deletion syndrome (3q29del) is associated with neuropsychiatric and neurodevelopmental phenotypes. We previously reported that graphomotor weakness is present in up to 78% of individuals with 3q29del. We have now explored nuances of the graphomotor phenotype and its association with other comorbidities in this population. Participants were recruited from the online 3q29 registry (3q29deletion.org) for two days of deep phenotyping. 32 individuals with 3q29del (62.5% male) were evaluated with the Be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The clinical phenotype of 3q29del is heterogeneous, ranging from mild to moderate intellectual disability (ID) (Ballif et al, 2008; Cox & Butler, 2015; Glassford et al, 2016; Klaiman et al, 2022; Sanchez Russo et al, 2021; Willatt et al, 2005) to a 19-fold increased risk for autism spectrum disorder (ASD) (Itsara et al, 2009; Pollak et al, 2019; Sanders et al, 2015) and a greater than 40-fold increased risk for schizophrenia spectrum disorders (SZ) (Kirov et al, 2012; Marshall et al, 2017; Mulle, 2015; Mulle et al, 2010; Szatkiewicz et al, 2014). Recent work by our team has uncovered additional phenotypes associated with 3q29del, including attention deficit/hyperactivity disorder (ADHD) and graphomotor weakness (Klaiman et al, 2022; Pollak et al, 2023b; Sanchez Russo et al, 2021). Further, 47% of study participants were found to have clinically significant executive function deficits (Klaiman et al, 2022; Sanchez Russo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical phenotype of 3q29del is heterogeneous, ranging from mild to moderate intellectual disability (ID) (Ballif et al, 2008; Cox & Butler, 2015; Glassford et al, 2016; Klaiman et al, 2022; Sanchez Russo et al, 2021; Willatt et al, 2005) to a 19-fold increased risk for autism spectrum disorder (ASD) (Itsara et al, 2009; Pollak et al, 2019; Sanders et al, 2015) and a greater than 40-fold increased risk for schizophrenia spectrum disorders (SZ) (Kirov et al, 2012; Marshall et al, 2017; Mulle, 2015; Mulle et al, 2010; Szatkiewicz et al, 2014). Recent work by our team has uncovered additional phenotypes associated with 3q29del, including attention deficit/hyperactivity disorder (ADHD) and graphomotor weakness (Klaiman et al, 2022; Pollak et al, 2023b; Sanchez Russo et al, 2021). Further, 47% of study participants were found to have clinically significant executive function deficits (Klaiman et al, 2022; Sanchez Russo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%